Where Am I? Investigating Map Matching During Self‐Localization With Mobile Eye Tracking in an Urban Environment. Issue 5 (27th October 2013) - Kiefer, Peter; Giannopoulos, Ioannis; Raubal, Martin
Abstract Self‐localization is the process of identifying one's current position on a map, and it is a crucial part of any wayfinding process. During self‐localization the wayfinder matches visually perceptible features of the environment, such as landmarks, with map symbols to constrain potential locations on the map. The success of this visual matching process constitutes an important factor for the success of self‐localization. In this research we aim at observing the visual matching process between environment and map during self‐localization with real‐world mobile eye tracking. We report on one orientation and one self‐localization experiment, both in an outdoor urban environment. The gaze data collected during the experiments show that successful participants put significantly more visual attention to those symbols on the map that were helpful in the given situation than unsuccessful participants. A sequence analysis revealed that they also had significantly more switches of visual attention between map symbols and their corresponding landmarks in the environment, which suggests they were following a more effective self‐localization strategy.